Digitalization of Trademark Registration for MSMEs in Yogyakarta: Service Effectiveness and Efficiency Analysis - Khasna, Syarifa (Iapa Proceedings Conference, 2024)
This study aims to analyze the effectiveness and efficiency of digital transformation in the trademark registration process for MSMEs in Yogyakarta. The method used is descriptive qualitative, with data collected through interviews and observations of MSME actors and review of official documents. The results of the study indicate that although digitalization can accelerate the process and reduce manual bureaucracy, there are significant obstacles, such as low digital literacy and limited access to technology in remote areas. In addition, complex procedures and lack of technical assistance are still major challenges. This study contributes to providing strategic recommendations to the government to improve the quality of digital trademark registration services, especially by expanding digital training and simplifying procedures for MSMEs to be more competitive in the digital era